Factors that Influence Tourism Recovery, Post Disaster Earthquake in Sembalun Sub-District, East Lombok Regency - Muhammad Arif Fatini; Yori Herwangi (Built Environment Studies, 2022)
The impact of the earthquake in Lombok Island not only had an impact on community settlements, but also on tourism activities. Especially in Sembalun District, East Lombok, the impact can kill the economy of the community, since tourism is one of the main livelihoods of the people. The process of tourism recovery in Sembalun District shows different progress. Therefore, the purpose of this research is to compare the tourism performance before and after an earthquake—which was analyzed using comparative descriptive method. Furthermore, the next goal is to describe the recovery process of tourism in the aftermath of an earthquake, and identify factors that influence the achievement of tourism recovery using descriptive analysis. Based on the results of each purpose, it shows that there are several differences in the tourism performance before and after the earthquake; either it has better performance after the earthquake or worse. The process of tourism recovery is carried out differently— depending on the damage level. Nonetheless, there are several tourism objects that have not been recovered, such as Bale Adat. There are 4 factors that affect tourism recovery after an earthquake; physical factors, economic factors, social factors, and unique cultural factors.